Adaptation and Psychometric Evaluation of the Evidence-Based Practice Mentoring Scale into Turkish - Elanur Uludağ; Fadime Ulupınar; Yasemin Erden (Ebelik ve Sağlık Bilimleri Dergisi)
Objective: This study aimed to adapt the Evidence-Based Practice Mentorship Scale (EBP-Mentorship Scale) into Turkish and to evaluate its psychometric properties among Turkish nurses.Methods: This methodological study was conducted with 152 nurses between October 2022 and May 2023. The EBP-Mentorship Scale was translated into Turkish, and its content and construct validity were assessed. Confirmatory factor analysis (CFA) was performed to validate the factor structure. Reliability was evaluated using Cronbach’s alpha, Pearson’s correlation, and intra-class correlation coefficients (ICC).Results: The Turkish version of the EBP-Mentorship Scale retained the original 8 items and 1-factor structure. CFA results indicated a good model fit (χ2/df < 2, RMSEA < 0.08, CFI > 0.90, GFI > 0.90). The scale demonstrated high internal consistency (Cronbach’s alpha = 0.94) and strong test-retest reliability (r = 0.956, p < .01; ICC = 0.997). The average variance extracted (AVE = 0.535) and composite reliability (CR = 0.899) values were sufficient, indicating good convergent validity.Conclusion: The Turkish version of the EBP-Mentorship Scale is a reliable and valid tool for assessing EBP mentorship among Turkish nurses. Its use can enhance the implementation and evaluation of EBP mentoring programs in nursing practice.